Health Literacy among Visitors of District Polyclinics in Almaty, Kazakhstan - Gaukhar KAYUPOVA; Botagoz TURDALIYEVA; Kazbek TULEBAYEV; Tuyen Van DUONG; Peter Wushou CHANG; Diana ZAGULOVA (Tehran University of Medical Sciences, 2017)
Background: This study aimed to evaluate health literacy levels of patients in Almaty City, Kazakhstan and to identify socio-demographics and socio-economic factors related to their health literacy. Methods: An international survey instrument HLS-EU-Q developed by the European Health Literacy Consortium was used in a cross-sectional study with 1000 citizens in the Almaty City at the age of 18 and over who visited the outpatient departments in the polyclinics between Feb and Oct 2014. Results: There were 552 women and 446 men completed the survey, with mean ages as (41.8 ± 13.9) and (44.7 ± 15.2) yr old respectively, and women were significantly younger than men (P<0.001). Their general health literacy was (34.0 ± 8.6) for men and (33.49 ± 9.4) for women, without significant difference. In them, 15.5% or 30.0% were with inadequate or problematic health literacy. Multivariate linear regression analysis showed that higher general health literacy was positively and significantly associated with high self- assessed social status (B=3.86, P<0.001), ability to pay for medications (B=3.42, P<0.001), low frequency of watching health related TV programs (B=2.37, P<0.001), moderate community involvement (B=2.23, P=0.03). Conclusion: Specific demographic and socio-economic determinants related to health literacy were identified the first time in Kazakhstan. This would facilitate programs to improve health outcomes in Kazakhstan.